1955
DOI: 10.1002/ange.19550671902
|View full text |Cite
|
Sign up to set email alerts
|

Das Mülheimer Normaldruck‐Polyäthylen‐Verfahren

Abstract: Es wird dargelegt. wie man iiberhaupt im MUlheimer lnstitut zur Entdeckung des ,,Normaldruck-Povathylen-Verfahrens" gekommen ist, denn diese Entdeckungsgeschichte ist fur sich schon interessant und verdient es, festgehalten zu werden. Es werden weiter eine Reihe grundsatzlicher Angaben iiber das neue Verfahren und das neue Polyathylen gemacht. Doch miissen eine Reihe wichtiger Probleme, die bei der technischen Herstellung des MUlheimer Polyathylens eine Rolle spielen, unbehandelt bleiben. Dazu gehoren u. a. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
321
0
26

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(347 citation statements)
references
References 0 publications
0
321
0
26
Order By: Relevance
“…Instead, the formation of 1-butene due to chain cleavage after one olefin insertion was detected. 238 A systematic search for the reasons of the unexpected but highly useful reactivity revealed that traces of nickel were responsible and the term "nickel effect" was coined. This observation led to the foundations of Ziegler catalysts 239 and set the basis for a revolution in different areas of chemistry and, in particular, in organonickel chemistry.…”
Section: Tm-ch3 As Intermediates In Catalysismentioning
confidence: 99%
“…Instead, the formation of 1-butene due to chain cleavage after one olefin insertion was detected. 238 A systematic search for the reasons of the unexpected but highly useful reactivity revealed that traces of nickel were responsible and the term "nickel effect" was coined. This observation led to the foundations of Ziegler catalysts 239 and set the basis for a revolution in different areas of chemistry and, in particular, in organonickel chemistry.…”
Section: Tm-ch3 As Intermediates In Catalysismentioning
confidence: 99%
“…The active catalytic centre originated by both precursors is assumed to be the same (figure 1d) because the polyethylene obtained in the two cases is the same. By analogy with the Cossee-Arlman mechanism (Arlman & Cossee 1964;Cossee 1964), proposed for classical Ziegler-Natta catalysts (Ziegler et al 1955;Natta 1956;Busico et al 1999), as well as for metallocene catalysts (Resconi et al 2000;Kaminsky & Laban 2001), it is arbitrarily assumed that the catalytic centre contains a coordination vacancy (coloured shadow in figure 1d), where the olefin molecule can insert, and a growing hydrocarbon chain. However, the initiation steps leading to the formation of the active centres constituted a matter of debate for many years, and were the subject of many investigations, also by means of surface science methods (Groppo et al 2005b).…”
Section: (B) Mechanism Of Initiation Of Ethylene Polymerizationmentioning
confidence: 99%
“…The polyolefin industries began in the 1950s because of discoveries of TiCl 3 catalysts by Ziegler and Natta. [1][2][3][4] However, the catalyst activities and stereospecificities were so low that enormous effort was invested to increase them. In 1968, our discovery of an MgCl 2 -supported TiCl 4 catalyst 5 brought about a breakthrough and led to innovative improvement of the properties of the polyolefins and a drastic cut of the production costs of them.…”
Section: Introductionmentioning
confidence: 99%